2013
DOI: 10.1074/jbc.m113.515544
|View full text |Cite
|
Sign up to set email alerts
|

Elongation Factor-1α Is a Novel Protein Associated with Host Cell Invasion and a Potential Protective Antigen of Cryptosporidium parvum

Abstract: Background: Apicomplexan parasites, including Cryptosporidium, possess organelles associated with host cell invasion. Results: A chicken-derived monoclonal antibody inhibited host cell invasion by C. parvum. The corresponding antigen, which localizes to the apical region of the parasite, was identified as elongation factor-1␣ (EF-1␣). Conclusion: EF-1␣ mediates cryptosporidial cytoskeletal complex critical for host cell invasion. Significance: The findings suggest that cryptosporidial EF-1␣ could serve as a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 42 publications
2
47
1
1
Order By: Relevance
“…They also demonstrated binding of heparin to elongation factor 1␣, an adhesin previously implicated in the mediation of C. parvum invasion in vitro (49). In this study, we employed a more comprehensive methodology and independently demonstrated the role of sulfated GAGs during C. parvum attachment and infection.…”
Section: Discussionmentioning
confidence: 85%
“…They also demonstrated binding of heparin to elongation factor 1␣, an adhesin previously implicated in the mediation of C. parvum invasion in vitro (49). In this study, we employed a more comprehensive methodology and independently demonstrated the role of sulfated GAGs during C. parvum attachment and infection.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, EF-1α can bind actin filaments and microtubules and regulate their assembly and cross-linking (Yang et al 1990;Doyle et al 2011). The results of our previous study on C. parvum suggest that EF-1α is associated with the cytoskeleton at the apical region and is an essential component of the invasion apparatus of the parasite (Matsubayashi et al 2013). The distinct localization of EF-1α in zoites, i.e., on the apical membranes of C. parvum and in the conoid of E. acervulina, may be related to differences in the mechanism of invasion, considering that Eimeria sporozoites invade both T lymphocytes and intestinal epithelial cells, whereas C. parvum sporozoites infect only the surface microvilli of epithelial cells.…”
Section: Discussionmentioning
confidence: 89%
“…The E. acervulina antigen recognized by mAb 6D-12-G10 was identified via NH 2 -terminal amino acid sequencing in combination with liquid chromatography/tandem mass spectrometry (LC-MS/MS), as previously reported (Matsubayashi et al 2013). Briefly, for LC-MS/MS analysis, the positive spots detected in the 2-DE gel after staining with Coomassie blue (Bio-rad) were excised, digested with trypsin (Promega, WI, USA), and resolved via highperformance liquid chromatography on a C-18 column (0.1 × 50 mm; Michrom BioResources, MA, USA) coupled to a Q-TOF2 mass spectrometer equipped with a nanoelectrospray ionization source (Waters Micromass, McKinley Scientific, NJ, USA).…”
Section: Identification Of Proteinsmentioning
confidence: 87%
“…Functionally, EF‐1α is responsible for GTP‐dependent binding of aminoacylated tRNAs to the A site of ribosomes during biosynthesis of protein 8 . In addition, EF‐1α involved in regulation of wide range of biological processes, such as cell growth and proliferation, vesicular transmission and protein formation, development of mitotic apparatus, signal transduction, DNA replication/repair and apoptosis 9‐15 . Previous studies reported that EF‐1α proteins were presented in various parasites such as Trypanosoma brucei , 16 Trichomonas vaginalis , 17 Cryptosporidium hominis , 18 Clonorchis sinensis and Brugia malayi , 19,20 Echinococcus granulosus 21 and Giardia intestinalis 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was suggested that EF‐1α protein allied to the cytoskeleton in apex section of Cryptosporidium parvum ( C parvum ), building an important constituent of parasite's invasion apparatus. It was also reported that EF‐1α of C parvum played crucial role in mediating host cell entry by the parasite and could be a potential vaccine candidate against cryptosporidiosis 13 . However, in the case of H contortus , the biological functions of EF‐1α during parasite invasion and its effects on host immune cells are still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%